The acquisition of the Latvian language as the Second language at preschool age in theory and practice - Tomme-Jukēvica, Ingēra (Journal of Education Culture and Society, 2020)
In Latvia there are no substantial studies on bilingual preschool children’s Latvian language as the second language. The article provides an overview of the 20th–21st century linguistic theories in the context of child second language acquisition as well as raises awareness about their infl uence on and use in the learning of preschoolers whose second language is Latvian, carrying out content analysis of the Minority Preschool Education Program(with instruction in Russian), the Latvian Language Program of X preschool education establishment, teaching resources (teaching aid kits, didactic handouts) as well as the Latvian language as the second language study content.The conclusion is drawn that the theory of communicative competence and the systemic functional grammar theory prevail as well as the basic principles of the behavioral theory can be discerned. In the teaching resources and learning process it is advisable to more often incorporate the same language material repetition in different situations and new combinations. Consideration must be given to more positive and negative transfer (interference) emphasis. To prevent children’s errors it is advisable to provide and incorporate special exercises in the teaching resources as well as methodological recommendations for the Latvian language teachers.